Hand hygiene practices in extreme resource limited situations: an integrative review of the literature - Zimmerman, Peta-Anne; Basseal, Jocelyne M.; Dennis, Sophie; Salmon, Sharon (International Journal of Infection Control, 2022)
As the COVID-19 pandemic affects more than one hundred million people, worldwide prevention measures, particularly hand hygiene (HH), are crucial to control and limit spread of disease. Yet access to clean water and soap or hand sanitiser may be scarce or unattainable in some situations. This integrative review, based on the framework of Whittemore and Knafl and the quality assessment performed in-line with the Mixed Methods Assessment Tool, aims to identify alternative HH agents and water sources that have demonstrated some efficacy in extreme resource limited situations. Four articles met inclusion criteria, with agents that create friction and repurposed water identified as alternatives to soap and water or hand sanitiser, resulting in reduced microbial load. Sand combined with repurposed cooking water, for example, can be used as an alternate HH measure in extreme resource limitations. Long term effects on skin integrity, compliance, and sustainability of these strategies must be considered.